2021
DOI: 10.3390/m1182
|View full text |Cite
|
Sign up to set email alerts
|

Cis-Bis(2,2′-Azopyridinido)dicarbonylruthenium(II)

Abstract: An [Ru(apy)2Cl2] precursor (apy = 2,2′-azopyridine) in 2-methoxyethanol was heated under a pressurized CO atmosphere to afford a diradical complex, [Ru(apy·−)2(CO)2], containing one-electron-reduced azo anion radical ligands. The electronic states of the complex were characterized by spectroscopic techniques and computational studies. Magnetic measurements revealed the existence of antiferromagnetic interactions in the diradical complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…They reported a newly synthesized diradical neutral dicarbonylruthenium(II) complex, bearing two azopyridyl ligands coordinated as anion radicals, by introducing in its structure two CO molecules as ligand and reducing agents. Further magnetic studies on the complex revealed paramagnetic and antiferromagnetic interactions between the spins in each radical [21].…”
mentioning
confidence: 97%
“…They reported a newly synthesized diradical neutral dicarbonylruthenium(II) complex, bearing two azopyridyl ligands coordinated as anion radicals, by introducing in its structure two CO molecules as ligand and reducing agents. Further magnetic studies on the complex revealed paramagnetic and antiferromagnetic interactions between the spins in each radical [21].…”
mentioning
confidence: 97%